(3cJGH aj Yde GdMQhas
(3ChdgG (B:s
(3GdMeO ddg GdPj GWdY TeS CfhGQ GSQGQ GdMQha CeG HYO aEf GdYde YRjR aef CYRgG abO CYRg Gddg hCfG ChcP Ydi GdJdejP HGdhUjI aj GdYde EPG UGQ Edjg s
(3BNQgG (B:s
(3hgh ef cdGe GdTjN eMeO Hf UOQ GdOjf hcGf Pdc YfO fRGY hbY YfO LeGYI HGdbGgQI s
(3Vef eLehY , JQJjHgG (B: 14s
(3HgG fXGe GdJYbjHIs
(3hHgG hbaI cGJHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs